Implementation of Cambridge Curriculum in Improving Education Quality at Mts Muhammadiyah 2 Paciran: Implementasi Kurikulum Cambridge dalam Peningkatan Kualitas Pendidikan di SMP Muhammadiyah 2 Paciran - Nurmayanti, Anita; Catur Wahyuni, Hana (Journal of Islamic and Muhammadiyah Studies, 2025)
General Background: The demand for quality education in Islamic schools has driven the adoption of international curricula to meet global standards. Specific Background: Mts Muhammadiyah 2 Paciran integrates the Cambridge curriculum to improve its teaching and learning process while maintaining Islamic values. Knowledge Gap: Limited studies have explored how international curricula are implemented in Islamic-based schools in Indonesia. Aim: This study aimed to analyze the implementation of the Cambridge curriculum at Mts Muhammadiyah 2 Paciran and its contribution to educational quality. Results: The findings revealed that the Cambridge curriculum improved classroom management, student engagement, and academic outcomes. Novelty: The study highlights the adaptation of an international curriculum within a local Islamic education context. Implications: This research provides insights for other Islamic schools considering similar curriculum integration to enhance competitiveness and educational quality. Highlights:• Integration of international curriculum in Islamic school• Improvement in education quality through Cambridge curriculum• Adaptation strategies in local school context Keyword: Cambridge Curriculum, Islamic Education, Curriculum Implementation, Education Quality, School Management